SPACE LAW AND HUMAN RIGHTS - Hobe, Stephan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: international space law, consisting of five international agreements and 7 resolutions of the United Nations General Assembly does not contain directly any provision that would hint to human rights. It cannot however be realistically perceived that there is any field of international law that would not be affected by human rights. Space Law provides an opportunity to be influenced by human rights. Article III of the Outer Space Treaty of 1967 allows the application of other areas of international law, such as human rights, in case of this area not being mentioned by the lex specialis of space law. Research methods: general-scientific and special-legal methods of scientific knowledge, in particular: system-structural and functional methods, method of observation, method of generalization, methods of analysis and synthesis have been applied. Results: in this short paper it will be assessed under which circumstances and with which effect human rights can be applied to the lex lata of international space law. Discussion: should no help be provided to an astronaut in distress? Should not the behaviour of astronauts on board the international space station be directed by the idea of human rights? Shouldn’t in the future any living together of human beings on celestial bodies like Moon or Mars be directed through human rights?